A phase IIa study of afuresertib, an oral pan‐AKT inhibitor, in patients with Langerhans cell histiocytosis. Issue 5 (2nd November 2016) - Arceci, Robert J.; Allen, Carl E.; Dunkel, Ira J.; Jacobsen, Eric; Whitlock, James; Vassallo, Robert; Morris, Shannon R.; Portnoy, Alison; Reedy, Beth Ann; Smith, Deborah A.; Noble, Robert; Murnane, Amy; et al.
Abstract: Background: Langerhans cell histiocytosis (LCH) is a clonal neoplasm characterized by widely varied clinical presentations, including multisystem involvement and systemic inflammatory symptoms. The AKT pathway is relevant to survival and proliferation of dendritic cells, and is also often upregulated in hematopoietic malignancies. A clinical response in an adult patient with LCH participating in the first‐in‐human trial of afuresertib prompted this prospective trial. Procedure: The population in the current study included treatment‐naïve (n = 7) and recurrent/refractory patients with LCH (n = 10), who received oral afuresertib (125 mg). The majority of patients were treated for > 24 weeks, with four patients receiving treatment for > 48 weeks. Results: Pharmacokinetic analysis showed similar exposures in previously reported patients with other hematologic malignancies. Primary drug‐related toxicities included Grade 1/2 nausea, diarrhea, dyspepsia, and vomiting. Grade 3 toxicities included fatigue, diarrhea, and pain (one of each). Another severe adverse event involved soft tissue necrosis. The overall response rate in evaluable subjects was 33% in treatment‐naïve patients and 28% in patients with recurrent/refractory disease, which did not meet the predefined Bayesian criteria for efficacy. Conclusion: Afuresertib has clinical activity in some patients with newly diagnosed and advanced LCH.